Wood-plastic anti-collision plate and preparation method thereof
By constructing a wood-plastic composite anti-collision panel with multiple toughening systems and microporous structure, the problems of existing anti-collision panels in terms of lightweight, impact resistance and moisture and heat resistance are solved, and efficient lightweight and moisture and heat resistance are achieved, which is suitable for multi-scenario applications.
Patent Information
- Application Number
- CN202510871643.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-06-26
- Publication Date
- 2025-10-03
AI Technical Summary
Existing anti-collision plates have deficiencies in lightweight, impact resistance, and moisture and heat resistance, making it difficult to simultaneously meet the requirements of complex working conditions, limiting their application in multiple scenarios.
A multiple toughening system is constructed using components such as PVC resin, thermoplastic polyurethane, nano-calcium carbonate, and hydrophobic fumed nano-silica. A microporous structure is formed through supercritical carbon dioxide. Combined with microcapsule self-repairing technology and polyurethane waterproof coating, a lightweight, highly impact-resistant, and moisture- and heat-resistant wood-plastic composite anti-collision panel is formed.
It achieves a lightweight design, significantly reduces material density, improves impact resistance and moisture and heat resistance, provides long-term protection, and is suitable for a variety of complex environments.
Smart Images

Figure SMS_1
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of composite materials, in particular to a wood-plastic anti-collision plate and a preparation method thereof. Background Art
[0002] With the increasing demand for safety and protective equipment in transportation, construction, and other fields, traditional anti-collision panels have exposed numerous problems in practical application, such as excessive density, high transportation costs, insufficient impact resistance, and poor environmental adaptability. Although traditional metal anti-collision panels have good impact resistance, they are heavy, which not only increases transportation and installation costs, but also easily corrodes in hot and humid environments, resulting in a short service life. While ordinary wood-plastic anti-collision panels have certain lightweight advantages, they lack impact toughness and easily absorb water and expand in hot and humid environments, resulting in poor mechanical properties and making them difficult to meet the requirements of complex working conditions.
[0003] In the current pursuit of energy conservation, emission reduction, and sustainable development, the development of new anti-collision materials that combine lightweighting, high impact resistance, and moisture and heat resistance is urgently needed. Lightweight design reduces energy consumption during material transportation and installation, minimizing resource waste; high impact resistance effectively absorbs energy in collisions, protecting personnel and equipment; and excellent moisture and heat resistance ensures long-term stable operation in harsh environments such as humidity and high temperatures, avoiding safety hazards caused by material degradation. Currently, existing technologies on the market struggle to simultaneously meet these three key performance requirements, limiting the application of anti-collision panels in various scenarios. Summary of the Invention
[0004] In order to solve the above problems, one of the objects of the present invention is to provide a wood-plastic composite anti-collision board, which is composed of the following components in parts by mass: 13-17 parts of PVC resin, 18-22 parts of thermoplastic polyurethane, 6-8 parts of PVC-g-MAH, 3-4 parts of nano-calcium carbonate, 0.9-1.5 parts of hydrophobic fumed nano-silica, 1.6-2 parts of heat stabilizer, 5-7 parts of plasticizer, 2-3 parts of acrylic processing aid, 3-5 parts of lubricant, 23-43 parts of wood flour, and 4.5-7.5 parts of microencapsulated self-healing agent.
[0005] Preferably, the plasticizer is DOTP.
[0006] Preferably, the acrylic ester processing aid is ACR-401.
[0007] Preferably, the lubricant is at least one of glyceryl monostearate and polyethylene wax.
[0008] Preferably, the heat stabilizer is methyltin mercaptan heat stabilizer ZP-181.
[0009] Preferably, the wood powder is oak powder with a particle size of less than 150 μm. Small-particle oak powder can reduce melt flow resistance.
[0010] Preferably, the thermoplastic polyurethane is at least one of thermoplastic polyether polyurethane and thermoplastic polyester polyurethane.
[0011] Another object of the present invention is to provide a method for preparing a wood-plastic composite anti-collision board, comprising the following steps: Pre-treated wood flour; preparing microencapsulated self-healing agents; PVC resin, thermoplastic polyurethane, PVC-g-MAH, nano-calcium carbonate, hydrophobic fumed nano-silica, heat stabilizer, plasticizer, acrylic processing aid, and lubricant are pre-mixed for 5-10 minutes to obtain mixture A; pre-treated wood powder is continuously added to mixture A and mixed for 5-10 minutes, and then a microencapsulated self-healing agent is added and mixed for 3-5 minutes to finally obtain mixture B; mixture B is added to a twin-screw extruder; the twin-screw extruder is then heated to melt mixture B, supercritical carbon dioxide is injected into the molten mixture B, and the mixture is extruded by the twin-screw extruder, rapidly cooled, embossed, and sprayed with a polyurethane waterproof coating to obtain a finished product; wherein the temperatures of the zones of the twin-screw extruder are: the temperature of zone 1 is 140-150°C, the temperature of zone 2 is 160-180°C, the temperature of zone 3 is 170-190°C, the temperature of zone 4 is 160-170°C, and the temperature of the die head is 175-185°C.
[0012] Preferably, the steps of pretreating wood powder are as follows: drying 23 to 43 parts of wood powder by mass to a moisture content of less than 3% and setting aside; stirring 2 to 3 parts of silane coupling agent with 40 to 50 parts of 90 to 94 wt% ethanol water for 5 to 15 minutes to form a hydrolyzate; spraying the hydrolyzate evenly onto the surface of the dried wood powder, heating to 90 to 110° C., and mixing at a high speed of 800 to 1200 rpm for 10 to 20 minutes to allow the silane coupling agent to react with the hydroxyl groups on the surface of the powder to form a hydrophobic film, and then drying again at 60 to 80° C. for 1 to 2 hours to remove the ethanol water, so that the final moisture content of the pretreated wood powder is less than 1%.
[0013] Preferably, the preparation steps of the microencapsulated self-repairing agent are as follows: 80-100 parts of phenolic epoxy resin F-51, 3-6 parts of penetrant and 1-3 parts of penetrant JFC are mixed according to the weight parts, and shear emulsification is carried out at 1000-1400 r / min at 45-55 ° C for 10-20 minutes to form a uniform O / W emulsion; 1-3 parts of urea are mixed with 3.2-3.8 parts of 30-40 wt% formaldehyde aqueous solution, and the pH is adjusted to 8-9 and 65-7 with NaOH. The reaction was carried out at 5°C for 1.5-2.5 hours to generate a UF prepolymer. The UF prepolymer was added to the O / W emulsion, and then 100-150 parts of a 0.5-1.5 wt% NaCl aqueous solution was added, and the pH was adjusted to 3.5-4.0 with dilute HCl. The reaction was carried out at 55-65°C for 2-3 hours under stirring at 600-800 r / min. The mixture was cooled, filtered, and the residue was washed alternately with ethanol and water for 3-5 times, and vacuum dried at 35-45°C for 12-24 hours to obtain a microencapsulated self-healing agent.
[0014] The beneficial effects are: the present application provides a lightweight, highly impact-resistant and moisture- and heat-resistant wood-plastic anti-collision board, providing a long-term protection solution for moisture- and heat-sensitive damage scenarios; in terms of lightweighting: by injecting supercritical carbon dioxide into the twin-screw extrusion melting section, utilizing its excellent diffusivity and low surface tension, a uniform microporous structure is formed in the material matrix, and at the same time, low-density oak powder is used as a filling material to significantly reduce the overall density and achieve efficient weight reduction. In terms of high impact resistance: a multiple toughening system is constructed. First, the microporous structure assisted by scCO2 not only helps to reduce weight, but also improves the energy absorption capacity per unit thickness and enhances the toughness of the material. Secondly, an interpenetrating network structure is constructed by PVC resin and thermoplastic polyurethane to further enhance the impact resistance of the material. At the same time, the compatibilizer PVC-g-MAH is used. Its graft chain is well compatible with PVC resin, and the anhydride group can react with the -NH group in thermoplastic polyurethane to form an imide bond, thereby enhancing the interfacial bonding strength between the two. It can also react with the hydroxyl group of oak powder to firmly anchor the oak powder in the interpenetrating network. In addition, the silane coupling agent can also improve the bonding between wood powder and PVC resin and thermoplastic polyurethane. The interfacial compatibility between the esters improves toughness and impact resistance. Furthermore, acrylic processing aids interact with the PVC resin molecular chains through polar groups, reducing friction between PVC resin particles and accelerating the melt plasticization process. Their long molecular chains form a physical cross-linked network within the melt, enhancing matrix elasticity and further improving the toughness and impact resistance of the board. Finally, nano-calcium carbonate and hydrophobic fumed nano-silica act as rigid particles, exerting toughening and stress dispersion effects. Combined with microcapsule self-healing technology, when impact creates microcracks, the capsules rupture and release a phenolic epoxy resin repair agent, which self-repairs damage through flow penetration and curing reactions, significantly improving impact resistance and service life. Regarding heat and humidity resistance: oak powder is pre-treated with a silane coupling agent to form a hydrophobic film on the surface, effectively inhibiting moisture penetration. Hydrophobic fumed silica fills the matrix voids, constructing an internal hydrophobic network that blocks water vapor diffusion paths. Combined with a polyurethane waterproof coating sprayed on the finished surface, this creates a triple hydrophobic barrier, significantly improving the material's stability and durability in hot and humid environments. DETAILED DESCRIPTION
[0015] In order to make the objectives, technical solutions and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments so that those skilled in the art can understand the present invention more clearly.
[0016] The following embodiments are only used to illustrate the present invention, but are not intended to limit the scope of the present invention. Based on the specific embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention.
[0017] In the examples of the present invention, unless otherwise specified, all raw material components are commercially available products well known to those skilled in the art; in the examples of the present invention, unless otherwise specified, the technical means used are conventional means well known to those skilled in the art.
[0018] Source of raw materials: Polyvinyl chloride resin (PVC resin), models SG-3, SG-5, and SG-7, were purchased from Guangzhou Haoyun Chemical Co., Ltd. Thermoplastic polyether polyurethane, model TPU BASF Germany 1185A, purchased from Dongguan Heyue Plastic Chemical Co., Ltd. Thermoplastic polyester polyurethane, model TPU Bayer 385SX, was purchased from Suzhou Qihuida Engineering Plastics Co., Ltd. Maleic anhydride grafted polyvinyl chloride (PVC-g-MAH) was purchased from Dongguan Shenghao Plastic Raw Materials Co., Ltd.; Nano calcium carbonate was purchased from Ningbo Weiye Plastics Co., Ltd. Hydrophobic fumed nano-silica was purchased from Shandong Kasong New Materials Co., Ltd. Methyltin mercaptan thermal stabilizer ZP-181, CAS No. 57583-35-4, was purchased from Weifang Hanghao New Material Technology Co., Ltd. Plasticizer DOTP was purchased from Ningbo Senhong Plastics Co., Ltd.; Acrylate processing aid, model ACR-401, purchased from Shandong Yiyuan Chemical Plant; Glyceryl monostearate was purchased from Guangdong Jiadele Technology Co., Ltd.; Polyethylene wax was purchased from Shanghai Xinnuo Chemical Co., Ltd. Oak powder with a particle size of less than 150 μm was purchased from Nanning Senxiong Wood Industry Co., Ltd. Silane coupling agents, models KH-550 and KH-560, were purchased from Shandong Yuanjin New Materials Co., Ltd. Novolac epoxy resin, model F-51, was purchased from Wuhan Lanabai Pharmaceutical Chemical Co., Ltd.; Emulsifier OP-10 was purchased from Hai'an Petrochemical Plant, Jiangsu Province; Penetrant JFC was purchased from Nantong Renda Chemical Co., Ltd. Polyurethane waterproof coating, purchased from Shandong Senmeite Waterproof Material Co., Ltd.; The remaining reagents are commercially available.
[0019] Example 1 This embodiment provides a wood-plastic composite anti-collision board, which is composed of the following components in parts by mass: 13 parts of PVC resin (type SG-5), 18 parts of thermoplastic polyester polyurethane, 6 parts of PVC-g-MAH, 3 parts of nano-calcium carbonate, 0.9 parts of hydrophobic fumed nano-silica, 1.6 parts of methyltin mercaptan heat stabilizer ZP-181, 5 parts of plasticizer DOTP, 2 parts of acrylic acid ester processing aid ACR-401, 3 parts of glycerol monostearate, 43 parts of oak powder with a particle size of less than 150 μm, and 4.5 parts of microencapsulated self-repairing agent; The method for preparing the wood-plastic composite anti-collision board comprises the following steps: The wood powder pretreatment steps are as follows: 43 parts by mass of oak powder with a particle size of less than 150 μm are dried to a moisture content of less than 3% and set aside; 2 parts of silane coupling agent KH-550 are stirred with 40 parts of 90wt% ethanol water for 5 minutes to form a hydrolyzed solution; the hydrolyzed solution is evenly sprayed onto the surface of the dried wood powder, the temperature is raised to 90°C, and high-speed mixing is performed at 80 rpm for 10 minutes to allow the silane coupling agent to react with the hydroxyl groups on the powder surface to form a hydrophobic film, and the mixture is dried again at 60°C for 1 hour to remove the ethanol water, so that the final moisture content of the pretreated wood powder is less than 1%; The steps for preparing a microencapsulated self-healing agent are as follows: 100 parts of phenolic epoxy resin F-51, 3 parts of penetrant, and 1 part of penetrant JFC are mixed according to weight parts, and shear emulsified at 1000 r / min at 45°C for 10 minutes to form a uniform O / W emulsion; 1 part of urea is mixed with 3.2 parts of a 30wt% formaldehyde aqueous solution, the pH is adjusted to 8 with NaOH, and the mixture is reacted at 65°C for 1.5 hours to generate a UF prepolymer; the UF prepolymer is added to the O / W emulsion, and then 100 parts of a 1.5wt% NaCl aqueous solution are added, the pH is adjusted to 3.5 with dilute HCl, and the mixture is reacted at 55°C for 2 hours under stirring at 600 r / min, cooled, filtered, and the residue is washed alternately with ethanol and water three times, and vacuum dried at 35°C for 12 hours to obtain a microencapsulated self-healing agent; 13 parts of PVC resin, 18 parts of thermoplastic polyester polyurethane, 6 parts of PVC-g-MAH, 3 parts of nano-calcium carbonate, 0.9 parts of hydrophobic fumed nano-silica, 1.6 parts of methyl tin mercaptan heat stabilizer ZP-181, 5 parts of plasticizer DOTP, 2 parts of acrylic acid processing aid ACR-401, and 3 parts of glycerol monostearate were pre-mixed for 5 minutes to obtain mixture A; pre-treated wood powder was added to mixture A and mixed for 5 minutes, and then 4.5 parts of microencapsulated self-repairing agent were added and mixed. 3 minutes to finally obtain mixture B; add mixture B into a twin-screw extruder; then heat the twin-screw extruder to melt mixture B, inject supercritical carbon dioxide into the molten mixture B, and extrude it through the twin-screw extruder, rapidly cool it, emboss it, and spray it with a 50μm polyurethane waterproof coating to obtain a finished product; wherein, the temperatures of each zone of the twin-screw extruder are: the temperature of zone 1 is 140°C, the temperature of zone 2 is 160°C, the temperature of zone 3 is 170°C, the temperature of zone 4 is 160°C, and the temperature of the die head is 175°C.
[0020] Example 2 This embodiment provides a wood-plastic composite anti-collision board, which is composed of the following components in parts by mass: 15 parts of PVC resin (model SG-5), 20 parts of thermoplastic polyether polyurethane, 7 parts of PVC-g-MAH, 3.5 parts of nano-calcium carbonate, 1.2 parts of hydrophobic fumed nano-silica, 1.8 parts of methyl tin mercaptan heat stabilizer ZP-181, 6 parts of plasticizer DOTP, 2.5 parts of acrylic acid ester processing aid ACR-401, 2 parts of glycerol monostearate, 2 parts of polyethylene wax, 33 parts of oak powder with a particle size of less than 150 μm, and 6 parts of microencapsulated self-repairing agent; The method for preparing the wood-plastic composite anti-collision board comprises the following steps: The steps of pretreating wood powder are as follows: 33 parts by mass of oak powder with a particle size of less than 150 μm are dried to a moisture content of less than 3% and set aside; 1.5 parts of silane coupling agent KH-550 and 1 part of silane coupling agent KH-560 are stirred with 45 parts of 92wt% ethanol water for 10 minutes to form a hydrolyzed solution; the hydrolyzed solution is evenly sprayed onto the surface of the dried wood powder, the temperature is raised to 100°C, and high-speed mixing is performed at 1000 rpm for 15 minutes to allow the silane coupling agent to react with the hydroxyl groups on the surface of the powder to form a hydrophobic film, and the powder is dried again at 70°C for 1.5 hours to remove the ethanol water, so that the final moisture content of the pretreated wood powder is less than 1%; The steps for preparing a microencapsulated self-healing agent are as follows: 90 parts by mass of phenolic epoxy resin F-51, 4.5 parts of penetrant, and 2 parts of penetrant JFC are mixed, and shear emulsified at 1200 r / min at 50°C for 15 minutes to form a uniform O / W emulsion; 2 parts of urea are mixed with 3.5 parts of a 35wt% formaldehyde aqueous solution, the pH is adjusted to 9 with NaOH, and the mixture is reacted at 70°C for 2 hours to generate a UF prepolymer; the UF prepolymer is added to the O / W emulsion, and then 125 parts of a 1wt% NaCl aqueous solution are added, the pH is adjusted to 4.0 with dilute HCl, and the mixture is stirred at 700 r / min and reacted at 60°C for 2.5 hours. The mixture is cooled, the residue is filtered, and the residue is washed alternately with ethanol and water four times, and vacuum dried at 40°C for 18 hours to obtain a microencapsulated self-healing agent; 15 parts of PVC resin, 20 parts of thermoplastic polyether polyurethane, 7 parts of PVC-g-MAH, 3.5 parts of nano calcium carbonate, 1.2 parts of hydrophobic fumed nano silica, 1.8 parts of methyl tin mercaptan heat stabilizer ZP-181, 6 parts of plasticizer DOTP, 2.5 parts of acrylic acid ester processing aid ACR-401, 2 parts of glycerol monostearate, and 2 parts of polyethylene wax were pre-mixed for 5-10 minutes to obtain a mixture A; the pre-treated wood powder was continuously added to the mixture A and mixed for 7.5 minutes, and then 6 parts of microencapsulated self- The repair agent is mixed for 4 minutes to obtain a mixture B; the mixture B is added to a twin-screw extruder; the twin-screw extruder is then heated to melt the mixture B, supercritical carbon dioxide is injected into the molten mixture B, and the mixture is extruded by the twin-screw extruder, rapidly cooled, embossed, and sprayed with a 10 μm polyurethane waterproof coating to obtain a finished product; wherein, the temperatures of each zone of the twin-screw extruder are: the temperature of zone 1 is 145°C, the temperature of zone 2 is 170°C, the temperature of zone 3 is 180°C, the temperature of zone 4 is 165°C, and the temperature of the die head is 180°C.
[0021] Example 3 This embodiment provides a wood-plastic composite anti-collision plate, which is composed of the following components in parts by mass: 17 parts of PVC resin (model SG-5), 11 parts of thermoplastic polyether polyurethane, 11 parts of thermoplastic polyester polyurethane, 8 parts of PVC-g-MAH, 4 parts of nano-calcium carbonate, 1.5 parts of hydrophobic fumed nano-silica, 2 parts of methyl tin mercaptan heat stabilizer ZP-181, 7 parts of plasticizer DOTP, 3 parts of acrylic ester processing aid ACR-401, 5 parts of polyethylene wax, 23 parts of oak powder with a particle size of less than 150 μm, and 7.5 parts of microencapsulated self-repairing agent; The method for preparing the wood-plastic composite anti-collision board comprises the following steps: The wood powder pretreatment steps are as follows: 23 parts by mass of oak powder with a particle size of less than 150 μm are dried to a moisture content of less than 3% and set aside; 3 parts of silane coupling agent KH-560 are stirred with 50 parts of 94wt% ethanol water for 15 minutes to form a hydrolyzed solution; the hydrolyzed solution is evenly sprayed onto the surface of the dried wood powder, the temperature is raised to 110°C, and high-speed mixing is performed at 1200 rpm for 20 minutes to allow the silane coupling agent to react with the hydroxyl groups on the surface of the powder to form a hydrophobic film, and the powder is dried again at 80°C for 2 hours to remove the ethanol water, so that the final moisture content of the pretreated wood powder is less than 1%; The steps for preparing a microencapsulated self-healing agent are as follows: 80 parts of phenolic epoxy resin F-51, 6 parts of penetrant, and 3 parts of penetrant JFC are mixed according to weight parts, and shear emulsified at 1400 r / min at 55°C for 20 minutes to form a uniform O / W emulsion; 3 parts of urea are mixed with 3.8 parts of 40wt% formaldehyde aqueous solution, the pH is adjusted to 8 with NaOH, and the mixture is reacted at 75°C for 2.5 hours to generate a UF prepolymer; the UF prepolymer is added to the O / W emulsion, and then 150 parts of 0.5wt% NaCl aqueous solution are added, the pH is adjusted to 3.5 with dilute HCl, and the mixture is stirred at 800 r / min and reacted at 65°C for 3 hours. The mixture is cooled, the filter residue is filtered, and the residue is washed alternately with ethanol and water five times, and vacuum dried at 45°C for 24 hours to obtain a microencapsulated self-healing agent; 17 parts of PVC resin, 11 parts of thermoplastic polyether polyurethane, 11 parts of thermoplastic polyester polyurethane, 8 parts of PVC-g-MAH, 4 parts of nano calcium carbonate, 1.5 parts of hydrophobic fumed nano silica, 2 parts of methyl tin mercaptan heat stabilizer ZP-181, 7 parts of plasticizer DOTP, 3 parts of acrylic ester processing aid ACR-401, and 5 parts of polyethylene wax were pre-mixed for 5-10 minutes to obtain a mixture A; the pre-treated wood powder was continuously added to the mixture A and mixed for 5-10 minutes, and then 7.5 parts of microencapsulated self- The repair agent is continuously mixed for 5 minutes to finally obtain a mixture B; the mixture B is added to a twin-screw extruder; the twin-screw extruder is then heated to melt the mixture B, supercritical carbon dioxide is injected into the molten mixture B, and the mixture is extruded by the twin-screw extruder, rapidly cooled, embossed, and sprayed with a 30 μm polyurethane waterproof coating to obtain a finished product; wherein, the temperatures of each zone of the twin-screw extruder are: the temperature of zone 1 is 150°C, the temperature of zone 2 is 180°C, the temperature of zone 3 is 190°C, the temperature of zone 4 is 170°C, and the temperature of the die head is 185°C.
[0022] Comparative Example 1 This comparative example differs from Example 2 in that PVC resin of type SG-7 is used instead of PVC resin of type SG-5. Other components and experimental steps are the same as those of Example 2.
[0023] Comparative Example 2 This comparative example differs from Example 2 in that PVC-g-MAH is not added, and the other components and experimental steps are the same as those in Example 2.
[0024] Comparative Example 3 This comparative example differs from Example 2 in that no acrylic acid ester processing aid is added, and the other components and experimental steps are the same as those in Example 2.
[0025] Comparative Example 4 This comparative example differs from Example 2 in that nano-calcium carbonate and hydrophobic fumed nano-silica are not added, and the other components and experimental steps are the same as those in Example 2.
[0026] Comparative Example 5 This comparative example differs from Example 2 in that the oak powder is not pretreated, and the other components and experimental steps are the same as those in Example 2.
[0027] Comparative Example 6 This comparative example differs from Example 2 in that supercritical carbon dioxide is not injected into the melted mixture B. Other components and experimental steps are the same as those in Example 2.
[0028] Performance testing: The anti-collision plates prepared in Examples 1 to 3 and Comparative Examples 1 to 6 of the present application were tested respectively, and the measurement method is as follows: Impact strength test is carried out in accordance with GB / T1843-2008; The static bending strength is tested in accordance with GB / T 17657-2013; The water absorption thickness expansion rate is tested according to the method of GB / T 24137-2009 "Test for water absorption performance of wood-plastic materials". The thickness expansion rate is measured after the sample is completely immersed in water for 24 hours; The dimensional change rate upon heating is tested in accordance with the GB / T 24137-2009 method. The dimensional change rate is measured after the sample is heated in an environment of (80±2)℃ for 24 hours. Density is tested in accordance with GB / T 35463-2017 “Determination of bulk density of wood-plastic composite materials and products”; Table 1 Anti-collision plate performance test results
[0029] From the above experimental data, the impact strength of the anti-collision panels prepared in Examples 1 to 3 of the present application is all above 35kJ / m², the static bending strength is greater than 50MPa, the 24h water absorption thickness expansion rate is less than 5%, the 24h heating dimensional change rate is less than 3%, and the density is less than 0.7. It can be seen that the wood-plastic composite anti-collision panels produced in each embodiment have lightweight, high impact resistance and moisture and heat resistance. The high impact resistance is mainly due to the multiple toughening systems constructed in the embodiment, including the microporous structure formed by supercritical carbon dioxide injection, which improves the energy absorption capacity per unit thickness; the interpenetrating network structure constructed by PVC resin and thermoplastic polyurethane improves the impact resistance; the compatibilizer PVC-g-MAH enhances the interface bonding strength and firmly anchors the oak powder; the physical cross-linking network formed by the acrylic ester processing aid enhances the elasticity of the matrix; nano-calcium carbonate and hydrophobic gas-phase nano-silica play a toughening and stress dispersion role; and the microcapsule self-repairing technology releases a repair agent when microcracks are generated by impact to further improve the impact resistance; the synergistic effect of each component makes the board have better mechanical properties, can effectively bear and disperse external forces, and improve the material's resistance to bending damage. In addition, each embodiment has good moisture and heat resistance, mainly because each embodiment adopts multiple hydrophobic measures, including a hydrophobic film on the surface of the oak powder pretreated with a silane coupling agent, an internal hydrophobic network constructed by hydrophobic gas-phase nano-silica filling, and a polyurethane waterproof coating sprayed on the surface of the finished product, which together form a triple hydrophobic barrier, effectively blocking moisture penetration and preventing the material from absorbing water and swelling, while ensuring that the internal network structure of the material is stable, the components are tightly combined, and it is not easy to change size when heated.
[0030] In Comparative Example 1, the use of SG-7 PVC resin instead of SG-5 PVC resin resulted in a significant decrease in impact strength and static flexural strength. This is likely due to the low degree of polymerization, short molecular chains, poor flexibility, and high brittleness of SG-7 PVC resin, resulting in a reduction in impact strength to 8.3 kJ / m² and static flexural strength to 18.5 MPa. When impacted, the molecular chains are unable to absorb energy through deformation, making the sheet susceptible to crack propagation. In Comparative Example 2, which did not include PVC-g-MAH, the impact strength was only 7.1 kJ / m², and the thickness expansion rate increased to 1.43%. This indicates that the interpenetrating network between the PVC resin and the thermoplastic polyurethane cannot form, resulting in poor interfacial bonding strength. This prevents the oak powder from being firmly anchored in the interpenetrating network, leading to agglomeration. Comparative Example 3 does not add acrylic processing aids, and lacks the physical cross-linking network formed by them, resulting in poor matrix elasticity, an impact strength of only 30.8 kJ / m², and a static bending strength of only 43.3 MPa, which are significantly lower than those of the examples. However, because it contains other toughening ingredients such as microencapsulated self-healing agents, its impact strength is still higher than that of Comparative Examples 1 and 2. Comparative Example 4 does not add nano-calcium carbonate and hydrophobic fumed nano-silica, and its impact strength is only 27.6 kJ / m², and the water absorption thickness expansion rate rises to 1.21%. This may be because nano-calcium carbonate and fumed nano-silica, as rigid particles, improve the toughness of the sheet and disperse the impact stress through stress dispersion and crack deflection mechanisms. At the same time, hydrophobic fumed silica fills the voids in the matrix, constructs an internal hydrophobic network, and blocks the water vapor diffusion path. After the two are missing, the toughening mechanism of the sheet fails, and moisture easily penetrates into the interior of the sheet in a hot and humid environment, resulting in interface debonding. In Comparative Example 5, the wood powder was not pretreated, resulting in a board with a water absorption expansion rate of 1.35% and a heating dimensional change rate of 1.09%. This is likely due to the silane coupling agent pretreatment, which forms a hydrophobic film on the wood powder surface, inhibiting water adsorption. The hydroxyl groups in the untreated wood powder readily form hydrogen bonds with water, causing the board to expand in volume after absorbing water. Furthermore, under hot and humid conditions, the expansion of the wood powder causes cracking in the resin matrix, resulting in poor dimensional stability. In Comparative Example 6, supercritical carbon dioxide was not injected, preventing the formation of a microporous structure to enhance energy absorption. The impact strength dropped to 23.9 kJ / m², and the board became a solid structure, resulting in a board density increase of 1.14 g / cm³.
[0031] The above data demonstrates that the wood-plastic composite anti-collision panel and its preparation method proposed in this application effectively achieve lightweight design while maintaining high impact resistance and excellent moisture and heat resistance. The mechanisms of action of each component and key process step are clearly defined; the absence of any key component or omission of any key process step will result in a cascading collapse in product performance.
[0032] The above is merely an embodiment of the present invention and is not intended to limit the present invention. It will be apparent to those skilled in the art that various modifications and variations of the present invention are possible. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention shall be included within the scope of the claims of the present invention.
Claims
1. A wood-plastic composite anti-collision plate, characterized in that: The composition is composed of the following components in parts by mass: 13~17 parts of PVC resin, 18~22 parts of thermoplastic polyurethane, 6~8 parts of PVC-g-MAH, 3~4 parts of nano-calcium carbonate, 0.9~1.5 parts of hydrophobic fumed nano-silica, 1.6~2 parts of heat stabilizer, 5~7 parts of plasticizer, 2~3 parts of acrylic processing aid, 3~5 parts of lubricant, 23~43 parts of wood flour, and 4.5~7.5 parts of microencapsulated self-healing agent.
2. The wood-plastic composite anti-collision plate according to claim 1, characterized in that: The plasticizer is DOTP.
3. The wood-plastic composite anti-collision plate according to claim 1, characterized in that: The acrylic acid ester processing aid is ACR-401.
4. The wood-plastic composite anti-collision plate according to claim 1, characterized in that: The lubricant is at least one of glyceryl monostearate and polyethylene wax.
5. The wood-plastic composite anti-collision plate according to claim 1, characterized in that: The heat stabilizer is methyltin mercaptan heat stabilizer ZP-181.
6. The wood-plastic composite anti-collision plate according to claim 1, characterized in that: The wood powder is oak powder with a particle size of less than 150 μm.
7. The wood-plastic composite anti-collision plate according to claim 1, characterized in that: The thermoplastic polyurethane is at least one of thermoplastic polyether polyurethane and thermoplastic polyester polyurethane.
8. The method for preparing the wood-plastic composite anti-collision plate according to any one of claims 1 to 7, characterized in that: The following steps are involved: pretreating the wood flour; preparing the microencapsulated self-repairing agent; The PVC resin, thermoplastic polyurethane, PVC-g-MAH, nano-calcium carbonate, hydrophobic fumed nano-silica, heat stabilizer, plasticizer, acrylic processing aid, and lubricant are pre-mixed for 5-10 minutes to obtain a mixture A; the pretreated wood powder is continuously added to the mixture A and mixed for 5-10 minutes, and then the microencapsulated self-repairing agent is added and mixed for 3-5 minutes to finally obtain a mixture B; the mixture B is added to a twin-screw extruder; the twin-screw extruder is then heated to melt the mixture B, supercritical carbon dioxide is injected into the melted mixture B, and the mixture is extruded by the twin-screw extruder, rapidly cooled, embossed, and sprayed with a polyurethane waterproof coating to obtain a finished product; wherein the temperature of each zone of the twin-screw extruder is: the temperature of zone 1 is 140-150°C, the temperature of zone 2 is 160-180°C, the temperature of zone 3 is 170-190°C, the temperature of zone 4 is 160-170°C, and the die head temperature is 175-185°C.
9. The method for preparing the wood-plastic composite anti-collision plate according to claim 8, characterized in that: The wood powder is pretreated as follows: 23 to 43 parts of the wood powder are dried to a moisture content of less than 3% by weight and set aside; 2 to 3 parts of the silane coupling agent are stirred with 40 to 50 parts of 90 to 94 wt% ethanol water for 5 to 15 minutes to form a hydrolyzate; the hydrolyzate is evenly sprayed onto the surface of the dried wood powder, the temperature is raised to 90 to 110° C., high-speed mixing is performed at 800 to 1200 rpm for 10 to 20 minutes, and the ethanol water is removed again by drying at 60 to 80° C. for 1 to 2 hours, so that the final moisture content of the pretreated wood powder is less than 1%.
10. The method for preparing the wood-plastic composite anti-collision plate according to claim 8, characterized in that: The preparation steps of the microencapsulated self-repairing agent are as follows: 80-100 parts of phenolic epoxy resin F-51, 3-6 parts of penetrant and 1-3 parts of penetrant JFC are mixed according to weight parts, and shear emulsification is carried out at 1000-1400 r / min at 45-55° C. for 10-20 minutes to form a uniform O / W emulsion; 1-3 parts of urea are mixed with 3.2-3.8 parts of 30-40 wt% formaldehyde aqueous solution, and the pH is adjusted to 8-9 with NaOH, and the reaction is carried out at 65-75° C. 1.5-2.5h to generate a UF prepolymer; the UF prepolymer is added to the O / W emulsion, and then 100-150 parts of a 0.5-1.5wt% NaCl aqueous solution is added, the pH is adjusted to 3.5-4.0 with dilute HCl, and the mixture is stirred at 600-800r / min and reacted at 55-65°C for 2-3h, cooled, filtered to obtain a residue, washed alternately with ethanol and water for 3-5 times, and vacuum dried at 35-45°C for 12-24h to obtain the microencapsulated self-healing agent.
Citation Information
Cited By
Antibacterial wood-plastic composite material for furniture customization and preparation method thereof
CN121406055A